Starring Red Wing! : The Incredible Career of Lilian M. St. Cyr, the First Native American Film Star - Waggoner, Linda M. (Book collections on Project MUSE., 2019)
"Starring Red Wing! is a sweeping narrative of St. Cyr's evolution as America's first Native American film star, from her childhood through her performance career, and to her days as a respected elder of the multi-tribal New York City Indian Community"--